If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(P)=(9)+(5)-(9P^5)
We move all terms to the left:
(P)-((9)+(5)-(9P^5))=0
We do not support ePpression: P^5
| 2/7+r=3/4 | | .04b+13=0.4b-8.6 | | w/2-39/4=53 | | 5n-9=-16+6n | | 36m-9=18m+6 | | 9x-5=8(x-8)-9 | | 65/m=m/25=1.625/m | | 12x-20+4=0 | | 7x+90=(6x-1) | | (3x+2)(6x-1)=0 | | 2x+3=×-5 | | 5x+5x+3+7=6x+4+3x | | (3,0.5);b=1.5 | | 2/3x=7/15 | | 12-(4x-7)-33=8(7x+1) | | Y=2x(4)+3 | | -2-2/3x=10 | | 63w+11w=52w+121 | | 4x+4=3x1 | | 50x-5x+3x=2385000 | | 2/3(k-3)=2/3(2k+1) | | X^4-122x^2+121=0 | | 3t+1-8=-3 | | 28-(n-2)=5(n+5) | | x-x/3=7/15 | | 6(x-2)=7x+14 | | 10-3(m+6)=8 | | F(-5)=3x^2+2x-2 | | 55=15^x | | 0=20x-44-2x^2 | | 11y+39=72 | | 44=-7x+4x+8 |